2021
DOI: 10.3390/ma14154142
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microgroove Structure on Cutting Performance and Chip Morphology during the Turning of Superalloy Inconel 718

Abstract: This study designed a new microgroove cutting tool to machine Inconel 718 and focused on the effect of microgroove structure on the cutting performance and chip morphology during the turning. A comparative analysis of the cutting force, cutting temperature, tool life, tool wear, and chip morphology of the microgroove cutting tool and the original cutting tool was conducted. The main cutting force and temperature of the microgroove cutting tool were reduced by 12% and 12.17%, respectively, compared with the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The tool life of the micro-grooved cutting tool was 23.08% longer than that of a similar untreated tool. It also improves the process of chip destruction, which has a positive effect on the stability of the tool [27].…”
Section: Carbidementioning
confidence: 99%
“…The tool life of the micro-grooved cutting tool was 23.08% longer than that of a similar untreated tool. It also improves the process of chip destruction, which has a positive effect on the stability of the tool [27].…”
Section: Carbidementioning
confidence: 99%
“…Fatima et al [16] while optimising the machining process for structured cutting tool observed that structured cutting tool develop less flank wear than traditional cutting tool. Zou et al [17] studied the performance of structured tool in machining of inconel 718 alloy and identified that tool life was increased by 23% in comparison to traditional tool.…”
Section: Introductionmentioning
confidence: 99%